A stakeholder assessment of human–elephant conflict in Benin - DJAGOUN, CHABI A.M.S.; AKPONA, T. Jean Didier; Kassa, Barthelemy; GICHOHI, N; MURUTHI, P; Sinsin, Franck (My University, 2017)
This field note has been adapted from the report of the project on elephant related conservation work in the larger WAP landscape was implemented with the support of the African Wildlife Foundation in 2015. Some activities were conducted to gain more knowledge about the elephant conservation in Benin’s National Parks. Detailed data on human-elephant conflict were collected through participatory field work with the local communities and Park administration. We found fidelity in the traditional knowledge and the scientific data as the kernel density map generated from the elephant bio-monitoring data overlap perfectly with the elephant concentration zones and the zone identified by the local communities as high conflict zones. Elephants depopulation from poaching is high and thus a major concern for biodiversity conservation. Elephant conservation stakeholders as well as local community members warn that patrol efficiency is limited and the fragile link between population and Park will be broken. The study enabled decision makers to determine priority areas where elephant populations are more liable to become vulnerable as a result of HEC, especially as elephants migrate between protected areas and the WAP (W-Arly-Pendjari) complex. Some strategies for sustainable elephant conservation were proposed.
Keywords: Parks; wildlife; crop raiding; management